The relevance of surfaces contamination assessment in occupational hygiene interventions in case of exposure to chemicals - Viegas, Susana (2018)
Dermal exposure assessment is still not a priority in the intervention of occupational hygiene when assessing exposure to chemical substances. However, for some substances in specific occupational settings, dermal intake can be the most important exposure route. Skin contamination can occur from contact with contaminated surfaces. Thus, knowing the levels of the substance present on the surfaces of the workplace is an important tool to indirectly measure dermal exposure. This paper aimed to claim attention for the relevance of surfaces contamination assessment in the occupational hygiene interventions. An extensive search was performed to identify specific papers published after 2010, reporting data of surfaces contamination in the scope of occupational hygiene interventions. Twenty-seven papers were considered and, from those, 63% were devoted to antineoplastic drugs occupational exposure assessment. This short review allowed concluding that surfaces contamination assessment is a very useful tool that, besides giving an indirect measure of dermal exposure, can also give relevant information to guide interventions to prevent exposure.